A numerical-experimental protocol to characterize corneal tissue with an application to predict astigmatic keratotomy surgery. (October 2017) - Ariza-Gracia, M.Á.; Ortillés, Á.; Cristóbal, J.Á.; Rodríguez Matas, J.F.; Calvo, B.
Abstract: Tonometers are intended to determine the intraocular pressure (IOP) and the quality of corneal tissue. In contrast to the physiological state of stress of the cornea, tonometers induce non-physiological bending stress. Recently, the use of a single experiment to calibrate a set of corneal mechanical properties was suggested to be an ill-posed problem. Thus, we propose a numerical-experimental protocol that uses inflation and indentation experiments simultaneously, restricting the optimization space to circumvent the ambiguity of the fitting. For the first time, both corneal behaviors, i.e., biaxial tension (physiological) and bending (non-physiological), are taken into account. The experimental protocol was performed using an animal model (New Zealand rabbit's cornea). The patient-specific geometry and IOP were registered using a MODI topographer (CSO, Italy) and an applanation tonometer, respectively. The mechanical response was evaluated using inflation and indentation experiments. Subsequently, the optimal set of material properties is identified via an inverse finite element method. To validate the methodology, an in vivo incisional refractive surgery (astigmatic keratotomy, AK) is performed on four animals. The optical outcomes showed a good agreement between the real and simulated surgeries, indicating that the protocol can provide a reliable set of mechanical properties that enables further applications and simulations. After a reliable ex vivo database of inflation experiments is built, our protocol could be extended to humans. Abstract : Highlights: Protocol to characterize the corneal behavior using inflation and indentation tests. A refractive surgery was used to validate the material parameters identified. Predicted visual correction was in agreement with experiments (error of −0.4 D). Patient-specific geometry are essential when validation criterion is optics. To extend protocol to humans, an ex-vivo database of inflation tests is required.